2019
DOI: 10.1002/app.47507
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and thermal expansion in large HDPE injection moldings

Abstract: Morphology and linear coefficients of thermal expansion (LCTE) within the wall of a large (10 kg) injection molded container were evaluated. The study employed polarized light microscopic birefringence techniques, differential scanning calorimetry, scanning electron microscopy (SEM), as well as thermal mechanical analysis to determine the LCTE anisotropy in the skin and core of the wall. A difference in crystallinity between skin and core was found, and a region with distinct lamellas was seen under SEM withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…The S1 region thickness estimated from the peak profile in the contour region was 240 μm < Δ x < 320 μm (as indicated by S1 in Figures a and a). The higher orientation layer induced by the shear force extended over distances of μm from the sample surface, which agreed with the features of the skin layers. , , ,, …”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…The S1 region thickness estimated from the peak profile in the contour region was 240 μm < Δ x < 320 μm (as indicated by S1 in Figures a and a). The higher orientation layer induced by the shear force extended over distances of μm from the sample surface, which agreed with the features of the skin layers. , , ,, …”
Section: Resultssupporting
confidence: 69%
“…The higher orientation layer induced by the shear force extended over distances of μm from the sample surface, w h i c h a g r e e d w i t h t h e f e a t u r e s o f t h e s k i n layers. 2,[5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22][23][24]26,27 As shown by SS1-1 and SS1-2 in Figure 3a, we found relatively high-intensity areas in the interior of the skin layer, although the intensity was lower than that of S1. Previous studies reported microscopic images of oriented molecular chains forming layers inside the skin layer.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation